ISLAM OF THE ERA OF MUHAMMAD SAW STUDY: THE HISTORY OF ISLAMIC CIVILZATION - Khaliza, Reza; Meidianti, Widyatna Zakirah; Daulay, Riski (Indikator Pendidikan Indonesia, 2023)
The life of the Arab nation changed after the sending of the Prophet of the end of time, the reformer of Islam, who brought goodness to the whole world, Prophet Muhammad SAW. Islamic values taught by the Prophet SAW. bring to the truth and release them from dishonorable behavior, such as worshiping idols and fighting among themselves for no apparent reason. The Prophet Muhammad SAW was sent by Allah to bring Islam by upholding moral civilization. Such was the condition of Mecca and its surroundings at that time. This study used a qualitative research method which in general this research was carried out by not going into the field in finding the source of the data. This research can also be interpreted as research that is carried out only based on written works, including research results, both those that have been and those that have not been published. Library research is also a literature study, namely exploring previous research to be continued or criticized and aims to collect data and information using various materials found in the library room such as books, magazines, journal documents, historical stories and others.